A Cumulative Study of Performance Degrading Factors in a High Capacity Cellular Zone System - Rajeev Kumar Mital; Umesh Kumar (Active and Passive Electronic Components)
In high capacity cellular zone systems, cell size is reduced considerably: hence cells may be re-defined as microcells. The key point in microcell interference modeling is that the desired signal, as wall as co-channel interferers' signals should have different statistics. A microcell interference model that which provides different fading parameters to the concerned signals is used in this paper to evaluate various performance degrading factors. Outage probability and spectrum efficiency have been calculated. Various techniques to counteract the above mentioned interferences have been suggested.